2017
DOI: 10.1016/j.surg.2016.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-day and appendicitis: Impact on management and outcomes

Abstract: Background Observational research has shown that delayed presentation is associated with perforation in appendicitis. Many factors that impact the ability to present for evaluation are influenced by time-of-day; for example, child care, work, transportation, and primary care office hours. Our objective was to evaluate for an association between care processes or clinical outcomes and presentation time. Methods Prospective cohort of 7,548 adults undergoing appendectomy at 56 hospitals across Washington State.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…Unfortunately, the retrospective nature of this study prohibits confirmation of this supposition. The time of patient presentation has been found to influence the process of care for human surgical patients 29 . Further investigation of the influence of process of care on feline morbidity associated with emergency surgical intervention is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the retrospective nature of this study prohibits confirmation of this supposition. The time of patient presentation has been found to influence the process of care for human surgical patients 29 . Further investigation of the influence of process of care on feline morbidity associated with emergency surgical intervention is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 28% of all patients who failed NOM during admission had a perforation sometime between CT scan and operative exploration, underscoring one of the inherent risks of NOM. Although nighttime admission was not associated with adverse events, there was an association between weekend admission and infectious complications, which may have been influenced by the presence of fewer personnel on weekends and changes in processes of care, as described by Drake et al (19). However, nighttime and weekend admission did not appear to influence protocol compliance.…”
Section: Discussionmentioning
confidence: 84%
“…[16] A study conducted with stroke patients found that patients with daytime and nighttime strokes had similar demographics; and another study found that appendicitis patients' clinical, demographic and socioeconomic statuses did not differ between different times-of-presentation. [17,18] Finally, a study conducted in an accident and emergency department found no gender variations in temporal attendance patterns. [19] These fi ndings suggest that demographics are typically similar regardless of when a patient presents to the ED within a 24-hour time period.…”
Section: Discussionmentioning
confidence: 96%